PRINSIP KESANTUNAN PADA FILM 99 NAMA CINTA KARYA DANIAL RIFKI SERTA RELEVANSINYA DENGAN PEMBELAJARAN BAHASA INDONESIA DI MADRASAH ALIYAH - Candra Alfiyani; Ika Martanti Mulyawati (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2022)
This study examines the principle of politeness in the film 99 Nama Cinta by Danial Rifki.The aims of this study are (1) to determine the politeness principles contained in Danial Rifki's film 99 Nama Cinta, (2) to determine the relevance of Danial Rifki's film 99 Nama Cinta to learning Indonesian at Madrasah Aliyah. This study uses a qualitative description method and uses a pragmatic approach. Data collection techniques used are listening techniques, note-taking techniques, and pause or pause techniques. The results of this study indicate that (1) Language politeness in Danial Rifki's film 99 Nama Cinta found 65 data including 40 data on compliance with language politeness consisting of 5 maxims of wisdom, 6 maxims of generosity, 20 maxims of appreciation, 3 maxims of simplicity, 4 maxim of consensus, 2 maxims of sympathy. There are 25 violations in the film 99 Nama Cinta, consisting of 3 violations of the maxim of wisdom, 1 violation of the maxim of generosity, 11 violations of the maxim of appreciation, 4 violations of the maxim of simplicity, 4 violations of the maxim of consensus, and 2 violations of the maxim of sympathy. (2) Relevance in learning Indonesian at Madrasah Aliyah, at KD 4.16 Prepare a review by taking into account the results of the comparison of several review texts. The film 99 Names of Love can be relevant in this learning as a learning medium for students to be able to compose review texts according to the systematics of reviewers.